Genome mapping of an apple scab, a powdery mildew and a woolly apple aphid resistance gene from open-pollinated Mildew Immune Selection - Bus, V.; Bassett, H.; Bowatte, D.; Chagné, D.; Ranatunga, C.; Ulluwishewa, Dulantha; Wiedow, C.; Gardiner, S. (2010)
Apple is host to a wide range of pests and diseases, with several of these, such as apple scab, powdery mildew and woolly apple aphid, being major causes of damage in most areas around the world. Resistance breeding is an effective way of controlling pests and diseases, provided that the resistance is durable. As the gene pyramiding strategy for increasing durability requires a sufficient supply of resistance genes with different modes of action, the identification and mapping of new resistance genes is an ongoing process in breeding. In this paper, we describe the mapping of an apple scab, a powdery mildew and a woolly apple aphid gene from progeny of open-pollinated mildew immune selection. The scab resistance gene Rvi16 was identified in progeny 93.051 G07-098 and mapped to linkage group 3 of apple. The mildew and woolly aphid genes were identified in accession 93.051 G02-054. The woolly aphid resistance gene Er4 mapped to linkage group 7 to a region close to where previously the genes Sd1 and Sd2, for resistance to the rosy apple leaf-curling aphid, had been mapped. The mildew resistance gene Pl-m mapped to the same region on linkage group 11 where Pl2 had been mapped previously. Flanking markers useful for marker-assisted selection have been identified for each gene. © 2010 Springer-Verlag.